RESPONSE OF OAT CULTIVARS TO DIFFERENT SEEDING RATES - Basheer A. Abraheem; Bushra SH. J. ALobaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate vegetative growth indicators of four oat cultivars (Genzania, Shefa, Carrolup, and Hamel) at seeding rates of 80, 100, and 120 kg ha⁻¹ in a factorial experiment within a randomized block design during the winter season 2022-2023. Genzania showed significant superiority in leaf area, relative growth rate (0.0707 g g⁻¹ day⁻¹), and total dry mass (21.54 tons ha⁻¹). Shefa excelled in tiller count (365.10 tillers m⁻²), while Hamel exhibited superiority in stem diameter (5.68 mm), lower lodging index (39.90), and fewer effective tillers (88.10%). Seeding rate effects included increased plant height and total dry mass, with a rise in lodging index. The highest seeding rate (120 kg ha⁻¹) significantly outperformed in tiller count. Conversely, leaf area and effective tiller percentage decreased with higher seeding rates. The 80 kg ha⁻¹ seeding rate showed superiority in relative growth rate. Interaction between factors was significant for total dry mass and lodging index, with Genzania × 120 kg ha⁻¹ performing the best. Cultivars varied in vegetative growth responses to seeding rates.